ՀՀ պետական տեղեկատվական քաղաքականության հիմնական ուղղությունները - Մկրտչյան, Հայկուհի (YSU Journal of International Affairs, 2017)
In the modern information society in the context of regulation of social and political relations, state information policy plays an important role. Its effective implementation is especially relevant in the Republic of Armenia, where the creation of an information society takes place in difficult situations in the region, as well as in many domestic problems of the country, such as the contradictions and not advanced legal regulation of public relations in the information sphere, unequal support for the interests of the individual, society and State, non-competitiveness of Armenian news agencies and mass media.
Keywords: information, political system, information society, information security, state information policy